2000
DOI: 10.1021/jp001105r
|View full text |Cite
|
Sign up to set email alerts
|

An EXAFS Study of Nanocrystalline Yttrium Stabilized Cubic Zirconia Films and Pure Zirconia Powders

Abstract: Detailed EXAFS (extended X-ray absorption fine structure spectroscopy) measurements have been collected for two nanocrystalline forms of zirconia, namely, dense films of yttria-stabilized cubic zirconia (YSZ) and tetragonal phase powders of pure ZrO 2 . Zr and Y K edge EXAFS spectra for the YSZ films with grain sizes of 6, 15, and 240 nm showed no major differences with the corresponding spectra of the bulk counterpart. This is clear proof that these nanocrystalline films exhibit similar levels of disorder to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 82 publications
8
59
0
Order By: Relevance
“…As a side remark, we note that Rush et al 19 also reported a much reduced coordination number of 4 for the nearest O shell from the central Zr atom in nanocrystalline zirconia. However, the Zr-O and Zr-Zr distances of 2.13 and 3.41 Å, respectively, in their sample is substantially different from our values of 2.06-2.10 Å and 3.59-3.62 Å for the three pure-cubic-phase samples, respectively.…”
Section: Resultssupporting
confidence: 46%
“…As a side remark, we note that Rush et al 19 also reported a much reduced coordination number of 4 for the nearest O shell from the central Zr atom in nanocrystalline zirconia. However, the Zr-O and Zr-Zr distances of 2.13 and 3.41 Å, respectively, in their sample is substantially different from our values of 2.06-2.10 Å and 3.59-3.62 Å for the three pure-cubic-phase samples, respectively.…”
Section: Resultssupporting
confidence: 46%
“…36 This is in contrast with the conclusions reached by Rush et al on nanocrystalline YSZ films. 37 They found that the Zr and Y K edge EXAFS spectra for the YSZ films with grain sizes of 6, 15, and 240 nm showed no major differences with the corresponding spectra of the bulk counterpart. This is clear proof that these nanocrystalline films exhibit similar levels of disorder to that of large crystals.…”
Section: A Xanes: Qualitative Analysismentioning
confidence: 98%
“…8 As precise experimental atomic ordering data of nanostructured materials are still difficult to obtain, computationally based theoretical two-body radial structural analysis is an important tool to complement experimental determinations of the coordination and distribution of species. [29][30][31] A theoretical discrete radial distribution function is simply obtained here by analyzing the thermally equilibrated LMC configurations, as an average over all equivalent sites. Of further interest is to determine how defects and dopants associate in groups.…”
Section: Lattice Monte Carlo Approachmentioning
confidence: 99%